Implementation of Data Mining Grouping Product Order Distribution Center In PT. Indomarco Prismatama Medan Branch - Nico Setiawan; Paska Marto Hasugian (Information Technology and Science (ITScience), 2020)
Data mining is the technique of extracting previously unknown information in a set of data in the database. Data mining has been applied in various fields which require extracting information. One of them in groupings of data. Grouping is used to divide a set of data into several sections that are useful to more easily identify a class of data. Distribution companies can use groupings of one to determine the intensity of the volume of goods ordered. The study analyzes the application of data mining algorithms k-meansclustering to elicit information from the data ordering goods contained in centerPT distribution. Indomarco Prismatama Medan branch. That is by using a number of items and the total amount of the quantity of each item ordered.